2010
DOI: 10.1007/s10899-010-9210-4
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs About and Attitudes Toward Gambling in French-Speaking Switzerland

Abstract: The present study aims to analyze attitudes and beliefs of the French-speaking general Swiss population (n = 2500; female n = 1280; mean age = 43 years) as regards gambling, which are to date almost exclusively studied in the North American and Australian contexts. Beliefs related to gambling include the perception of the effectiveness of preventive measures toward gambling, the comparative risk assessment of different addictive behaviors, the perceived risks of different types of gambling and attitudes are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…This suggests that, in general, the sample were quite sensitive to problem gambling. These trends are in line with Inglin and Gmel (2011) findings on the Swiss Frenchspeaking population, who perceived gambling as being the third most serious addictive behavior (after drugs and alcohol, and before tobacco). Moreover, the majority (70 %) of their sample felt that information about the risks of gambling was needed.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This suggests that, in general, the sample were quite sensitive to problem gambling. These trends are in line with Inglin and Gmel (2011) findings on the Swiss Frenchspeaking population, who perceived gambling as being the third most serious addictive behavior (after drugs and alcohol, and before tobacco). Moreover, the majority (70 %) of their sample felt that information about the risks of gambling was needed.…”
Section: Discussionsupporting
confidence: 89%
“…It is also higher than that of males, from the canton of Neuchatel, in high-school and vocational training. However, the observed rate is equivalent to that observed in the general French-speaking population (56.8 %) (Inglin and Gmel 2011). Our findings support Luder et al (2010), who report that frequent gambling is highly prevalent in French-speaking Switzerland.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results showed that about 55% of the sample reported gambling in the previous twelve months. This prevalence is similar to the rates observed by Tomei et al (2014) in 18-22 year-old French-speaking men (56.1%) and by Inglin and Gmel (2011) in the French-speaking adult population (56.8%), suggesting that gambling is a popular activity in Switzerland. Moreover, although low, the prevalence of DSM-5 gambling disorder observed in the present study (1.0 of the total sample, 1.7% of gamblers) is slightly higher than the rates of pathological gambling (1.4% of gamblers) observed by Tomei et al (2014) in a comparable sample of Swiss French-speaking young men, and is about twice the prevalence of pathological gambling (0.5%) reported by Bondolfi et al (2008) in the Swiss adult population.…”
Section: Discussionsupporting
confidence: 83%
“…This explains partly why the number of peer-reviewed published papers authored by Swiss investigators to date is limited. Among studies published in the last 5 years, some have focused on the prevention, assessment and prevalence of problem offline and online gambling in the community [18,[38][39][40][41][42], while others were interested in risk factors associated with harmful gambling [43,44].…”
Section: Research Base and Research Agendamentioning
confidence: 99%